PENDEKATAN DENGAN KOMUNIKASI EFEKTIF TERHADAP KONSUMSI BUAH DAN SAYUR ANAK PRASEKOLAH (3-6 Tahun) BERDASARKAN TRANS TEORETHICAL MODEL - Yessy Nur Endah Sary (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
The low consumption of fruits and vegetables in preschool children can cause chronic diseases, lower immunity and digestive disorders in preschool children. The purpose of this study was to analyze the effect of effective communication on fruit and vegetable consumption of preschool children based on the transtheoretical model. This is research with a quasi-experimental design. The measuring instrument used in the study is a questionnaire that has been tested for validity and reliability. The questionnaire contains the daily consumption of fruits and vegetables, a checklist of effective communication steps for mothers, questionnaires for pre-contemplation, contemplation, preparation, action, maintenance stages. The sampling technique used is simple random sampling. The sample in the study was 15 people. Data analysis used the Independent Sample T-Test. The results showed that the average obtained was 3.82. The pre-test post-test gain value on Equal Variances assumed obtained a significance value of 0.003 (<0.05) so it can be concluded that there is a difference in the mean pre-test post-test so that there is a positive effect of the intervention on daily fruit and vegetable consumption. Table 4 above informs that all respondents (100%) entered the pre-contemplation stage, as many as 14 respondents (93.3%) went through the contemplation, preparation and action stages, and only 13 respondents (86.6%) reached the stage maintenance because 1 respondent (6.6%) had a relapse. The conclusion of this study is that effective communication affects vegetable consumption and preschool children based on the transtheoretical model.